An exploration of personal, relational and collective well-being in nursing students during their training at a tertiary education institution - Kirsten D. Watkins; Vera Roos; Engela Van der Walt (AOSIS, 2011)
The well-being of nursing students has become crucial because of the multidimensional challenges that nursing professionals have to deal with. A community psychology framework was adopted in this study. The aim of the research was to explore the different dimensions of well-being as described by nursing students. A purposive and availability sample was used to gather qualitative data (interviews, focus groups and visual presentations) during 2008 and 2010 from first-year nursing students, which were thematically analysed. The emergent themes were grouped according to personal, relational and collective well-being. The findings indicated that nursing students' personal well-being was undermined by a lack of autonomy, feelings of uncertainty, and feelings of pressure and disillusionment with the nursing profession and their training. Personal well-being was also described in terms of dispositional optimism and the need for a sense of purpose and deeper meaning. Relational well-being was expressed by the nursing students in relation to their friends, family and lecturers. The different relationships were important sources of comfort and encouragement. Their collective well-being was threatened by a challenging work environment, lack of role models in clinical settings as well as incongruence between theoretical training and practical application. Recommendations for improving the different dimensions of well-being are suggested. Opsomming Die welsyn van verpleegkundestudente het deurslaggewend geword as gevolg van die uiteenlopende uitdagings wat verpleegkundiges moet hanteer. 'n Gemeenskapsielkunde raamwerk is in hierdie studie gebruik. Die doel van die navorsing was om die verskillende dimensies van welsyn van verpleegkundestudente te ondersoek. 'n Doelgerigte en beskikbaarheidsteekproef is gebruik om kwalitatiewe data (onderhoude, fokusgroepe en visuele voorstellings) wat gedurende 2008 en 2010 van eerstejaar-verpleegkundestudente bekom is, deur middel van tematiese inhoudsontleding te analiseer. Die temas wat na vore gekom het, is gegroepeer volgens persoonlike, verhoudings- en gemeenskaplike welsyn. Die bevindinge het aangedui dat die verpleegkundestudente se persoonlike welsyn ondermyn word deur 'n gebrek aan outonomie, gevoelens van onsekerheid en om onder druk te verkeer, asook 'n ontnugtering met die verpleegkunde professie en opleiding. Persoonlike welyn is ook beskryf in terme van 'n optimistiese ingesteldheid en die behoefte aan sinvolheid en 'n dieper betekenis. Verhoudingswelsyn is deur die verpleegkundestudente uitgedruk in terme van hulle verhouding met hul vriende, familie en dosente. Die verskillende verhoudings word as belangrike bronne van ondersteuning en aanmoediging geag. Gemeenskaplike welsyn word bedreig deur 'n uitdagende werksomgewing, die afwesigheid van rolmodelle in die kliniese omgewings asook die teenstrydigheid van die teoretiese opleiding met die praktiese toepassing daarvan. Aanbevelings vir die bevordering van welsyn in die verskillende dimensies word voorgestel.